COLONIAL GAZES AND MYTHIC LANDSCAPES: A CRITICAL STUDY OF EUROPEAN TRAVELOGUES ON KASHMIR - Zahoor , Asiya (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Travel writing, particularly from the colonial period, has significantly influenced the ways in which places like Kashmir are imagined and understood. European travelogues on Kashmir are not just descriptive texts; they are a form of cultural production that participates in the broader discourse of colonial power, representing the region through a Western, often exoticized lens. These travelogues, while seemingly concerned with documenting landscapes and cultures, are deeply ideological, reflecting the colonial desire to construct and control the "other." This article situates European travel narratives on Kashmir within postcolonial and critical theoretical frameworks, exploring how these texts construct space, identity, and knowledge, and how these constructions perpetuate particular visions of the world.